2015
DOI: 10.1134/s0006297915050168
|View full text |Cite
|
Sign up to set email alerts
|

Pure mitochondrial DNA does not activate human neutrophils in vitro

Abstract: Excessive activation of the innate immune system often leads to fatal consequences and can be considered as one of the phenoptotic events. After traumatic injury, various components of mitochondria are released into the circulation and stimulate myeloid cells of the innate immunity. Presumably, mitochondrial DNA (mtDNA) might activate immune cells (Zhang, Q., et al. (2010) Nature, 464, 104-107). In the present study, we investigated the role of mtDNA as a direct activator of human neutrophils, as well as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has been shown that levels of mtDNA released into the circulation in trauma patients were markedly elevated in comparison with volunteers, and the released mtDNA induced sterile inflammation . In contrast, highly purified mtDNA was recently demonstrated to be unable to activate neutrophilic responses; thus, neutrophilic activation by mtDNA is now controversial. On the other hand, it is well known that various exogenous N ‐formylated peptides such as fMLF, which is a bacterial protein‐derived N ‐formylated peptide, can activate neutrophils; however, endogenous N ‐formylated peptides responsible for these immune responses in MTDs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that levels of mtDNA released into the circulation in trauma patients were markedly elevated in comparison with volunteers, and the released mtDNA induced sterile inflammation . In contrast, highly purified mtDNA was recently demonstrated to be unable to activate neutrophilic responses; thus, neutrophilic activation by mtDNA is now controversial. On the other hand, it is well known that various exogenous N ‐formylated peptides such as fMLF, which is a bacterial protein‐derived N ‐formylated peptide, can activate neutrophils; however, endogenous N ‐formylated peptides responsible for these immune responses in MTDs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, basal, unstimulated, NET formation in our experiments was already low, so that we could only identify a modest drop in NETosis from neutrophils of septic patients. This is interesting, as Zhang et al had shown that mitochondrial DAMPS, being a mixture of mtDNA and mitochondrial proteins stimulate neutrophils (12), whereas highly purified mtDNA alone, as we used it in our experiments, did not activate neutrophils (26). As we and others have shown recently, mtDNA can induce immunosuppressive phenotypes, by inhibiting cytotoxic T-cell activity, both in wildtype mice and humans with sepsis (12,13).…”
Section: Discussionmentioning
confidence: 56%
“…In addition, beyond ALX/FPR2, BOC‐2 may also exert antagonistic effects on FPR1. FPR1 induces neutrophil migration in response to circulating mitochondrial damage‐associated molecular patterns . The BOC‐2 effects can thus be explained by FPR1 signaling inhibition beyond antagonizing LXA 4 activity.…”
Section: Discussionmentioning
confidence: 99%